2010
DOI: 10.1007/s11340-010-9443-2
|View full text |Cite
|
Sign up to set email alerts
|

Modal Analysis of a Servo-Hydraulic High Speed Machine and its Application to Dynamic Tensile Testing at an Intermediate Strain Rate

Abstract: This paper describes the experimental procedure to identify the predominant frequencies of the high speed testing machine by conducting modal analysis. The effects due to the predominant frequencies of the system and loading rate on the magnitude of system ringing and the flow stress were analyzed by using a single degree-offreedom (SDOF) spring-mass-damper model. The system was then used to study the dynamic tensile behavior of two engineering materials, i.e., polyethylene (PE) fabric-cement composite and Alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Accordingly, the ram is programmed to be accelerated in the run-up. Solving the above equation, we obtain the following formulation: 11,19)…”
Section: Stress Oscillation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the ram is programmed to be accelerated in the run-up. Solving the above equation, we obtain the following formulation: 11,19)…”
Section: Stress Oscillation Modelmentioning
confidence: 99%
“…They used a linear regression method to evaluate the natural frequency of a compression test machine. Zhu et al 11) used an autoregressive method to fit the data and proposed spring-mass-damper model with a single degree of freedom to explain the elastic phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…E 33 is taken as zero simply because shell elements are used to model the fabric. The values for E 11 , E 22 , G 12 , G 31 , and G 23 are a function of several factors including current stress and strain, stress and strain history, and strain rate. The determination of these material properties will be discussed in the following section.…”
Section: Constitutive Behavior Of the Fabricmentioning
confidence: 99%
“…Yarn strength decreases slightly as the gage length increases; whereas the failure strain of the Kevlar ® 49 yarns was independent of the gage length, however decreased slightly as the strain rate increased. Zhu et al [8][9][10][11] conducted dynamic tensile testing on Kevlar ® 49 single yarn and fabrics using a servo-hydraulic high speed machine [12][13][14][15][16][17][18] and found that the Young's modulus, tensile strength, maximum strain and toughness increased with increasing strain rate over a range of 20 to 170 s -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, material properties not only for static, but also dynamic strain rates have to be known for complex analysis of car-body deformation components. The strain rate raising, resistance to deformation increases as well and some materials have shown material micro-and sub-structure change [1,2], yield strength and deformation to fracture growth [3].…”
Section: Introductionmentioning
confidence: 99%